Transcatheter bicuspid versus tricuspid aortic valve replacement in patients with a small aortic annulus: an observational study - Jun Chen; Qiong Liu; Xian-bao Liu; Wenjing Sheng; Jiaqi Fan; Chongzhou Zheng; Dao Zhou; Hanyi Dai; Junhui Xue (Open Heart)
Objective To compare the clinical outcomes and haemodynamic performance following transcatheter aortic valve replacement (TAVR) in patients with severe bicuspid versus tricuspid aortic stenosis (AS) and small annuli.Design Retrospective analysis based on a prospective observational cohort.Setting Single-centre registry of patients undergoing TAVR between 2016 and 2023.Participants A total of 427 patients (193 bicuspid (BAV) and 234 tricuspid (TAV) aortic valve) with symptomatic severe AS and small annuli (median area 381.5 mm2 (IQR 348.0–406.4)), all undergoing preprocedural multidetector CT and standardised follow-up echocardiography.Main outcomes measure Baseline characteristics, technical success, procedural complications, haemodynamic performance and bioprosthetic-valve dysfunction (BVD) were compared between groups. The primary clinical outcome was major adverse cardiac and cerebrovascular events (MACCE), a composite of all-cause mortality, stroke and rehospitalisation for heart failure.Cox regression was used to adjust for confounders.Results Compared with TAV patients, BAV recipients experienced higher technical failure rates (11.4% vs 6.0%, p=0.045) but lower permanent pacemaker implantation (4.7% vs 12%, p=0.008) at discharge. The 1-year MACCE rate was similar between groups (14.5% vs 9.8%, log-rank p=0.719), and Cox regression analyses adjusting for confounders revealed no significant difference (HR 1.408 (95% CI 0.622 to 3.191), p=0.412). Both groups demonstrated significant improvements in valve haemodynamics, with comparable rates of BVD (11.4% vs 9.2%, p=0.502) and structural valve dysfunction. Multivariate analysis demonstrated equivalent long-term survivals (HR 0.950 (95% CI 0.526 to 1.714), p=0.864) between groups.Conclusion TAVR provides comparable clinical and haemodynamic outcomes for bicuspid and tricuspid AS with a small aortic annulus, despite greater procedural complexity in BAV cases. These findings support cautious expansion of TAVR to select BAV patients when performed with meticulous procedural planning.